Atsaru Tathbiqi Wasail al-Ta’lim al-Raqmiyyah fi Tahsini Maharati al-Istima’ Lada Thalabati Ghurfati al-Lughat al-‘Arabiyyah fi Ma’hadi An-Nur Ats-Tsani fi Bululawang - Nailus Sa'adah; Nuril Mufidah (AlFaqrah: Journal of Arabic Studies, 2026)
This study aims to describe the use of podcasts in Arabic language teaching, identify their impact on improving students’ listening skills, and analyze the differences in students’ ability levels before and after the use of podcasts in the learning process. This research employed a quantitative approach with a quasi-experimental design using a one-group pre-test and post-test model. The population and sample of the study consisted of 15 Arabic language students at Anwar Al-Thani Institute in Malang, selected through a purposive sampling technique. Data were collected through pre-tests and post-tests to measure students’ listening skills before and after the implementation of podcasts. The data were analyzed using statistical techniques, including the calculation of the mean score and the t-test, to determine the significance of differences between the results before and after the treatment. The findings indicate that: (1) the use of podcasts significantly contributes to improving students’ listening skills; (2) this medium proves effective in helping students better understand Arabic audio materials; and (3) there is a statistically significant difference between the pre-test and post-test results after the implementation of podcasts in the learning process. Therefore, podcasts can be considered an innovative instructional medium that contributes to the development of Arabic language learning, particularly in enhancing students’ listening skills.